Use of umbilical cord blood culture in the diagnosis of early onset neonatal sepsis among high risk mothers - Ojha, Maitreyi; Pradhan, Ashish; Dutta, Sudip; Jaiswal, Anamika (Asian Journal of Medical Sciences, 2021)
Background: Early onset neonatal sepsis (EONS) is one of the important causes of morbidity and mortality in neonates. Its early diagnosis and prompt treatment is essential and any delay in the diagnosis can have serious consequences including neonatal death. Blood culture is the gold standard test for diagnosis of neonatal sepsis. Umbilical cord blood culture (UCBC) is a painless procedure and technically less challenging. We conducted this study to evaluate use of UCBC for the diagnosis of EONS and compared it with the results of peripheral venous blood culture (PVBC) reports. Aims and Objectives: The aim of the study was to evaluate UCBC for the diagnosis of EONS and compared it with the results of PVBC reports. Materials and Methods: This was a hospital-based prospective cohort study consisting of 100 neonates who were at risk of EONS. The study was conducted in the Department of Pediatrics Sikkim Manipal Institute of Medical Sciences Gangtok between January 2018 and December 2019. Neonates found to be at risk of development of EONS were included in this study on the basis of a predefined inclusion and exclusion criteria. Immediately after birth blood samples were collected from both umbilical cord and peripheral vein and were sent to bacteriology lab. Sensitivity, specificity, positive predictive value, and negative predictive value of both the samples were analyzed. Results: Out of 100 neonates in 32 (32%) EONS could be confirmed with positive sepsis screening results and/or demonstration of organisms on blood culture. Among the 32 neonates with EONS, 17 were found to be premature. The mean gestational age of newborns with EONS was found to be 35.2 weeks. The umbilical blood culture was found to have sensitivity and specificity of 100% and 74.4%, respectively, whereas peripheral vein blood culture was found to have sensitivity and specificity of 77.7% and 72.5%, respectively. The most common organism grown in our study was Escherichia coli. Conclusion: UCBC is painless and technically less challenging method of blood sampling. It has been found to have a higher sensitivity as well specificity for the diagnosis of EONS as compared to peripheral venous blood sample.